Nutraceutical analysis and formulation of edible tablet containing Phaleria macrocarpa (scheff.) boerl fruit - Noor Ezzuddin, Najat Nabilah (2021)
Phaleria macrocarpa is a recent emerging medicinal plant species with numerous nutraceutical prospects. The present study was undertaken to evaluate nutraceutical potentiality and formulate the species-based tablet as part of dietary supplements with a view of providing medical or health benefits, including the prevention and treatment of diseases. The primary aim of the study was to determine its antioxidant activities and their physicochemical properties, followed by optimization of formulation of tablets from fruit extract of P. macrocarpa. At the initiation of the study, proximate analyses showed that the extract consisted of 9.4%protein, 21.6%fibre, 5.6% oil, 88.4% moisture content, 10.9% dry matter and 6.3% ash content. The extract recorded antioxidant content of 80.1% free radical scavenging activity (1,1Diphenyl-1-picrylhydrazyl, DPPH) with 92.9% inhibitory concentration IC50 at concentration of 62.5ppm. Ferric reducing antioxidant power (FRAP), total phenolic content (TPC) and total flavonoid content (TFC) recorded values of 5199.02 Fe2+/100 mL, 369.1 mg GAE/g, and 89.89 mg QE/100 mL respectively. In the meantime, total anthocyanin, total carotenoid and total phosphomolybdenum yielded 0.49926 mg/L, 0.29 g BET/100g, and 0.05 mg GAE/mL respectively. The study observed that beta-carotene degradation rate increased with decrease in concentration of extract. Cytotoxicity test carried out using MCF-7 cells, MDA-MB-231cells and A549 cells, showed that methanolic extract gave positive results towards all cells with IC50 of 280 μg/mL and 25 μg/mL (hexane extract) for MCF-7 cells, 210 μg/mL for MDA-MB-231 cells, and 70 μg/mL for A549 cells. Brine shrimp lethality dose recorded 10% mortality rate at highest extract concentration of 1000 ppm. However, antidiabetic and antimicrobial activity of the extract did not produce any positive results. In tablet formulation, the effects of maltodextrin, guar gum, and microcrystalline cellulose (MCC) were observed on tablet hardness and fracturability using statistical D-optimal mixture design software and tested using Texture Analyser. The best performance in hardness and fracturability of the tablet was a mixture of 5.028% maltodextrin, 0.472% guar gum, and 34% MCC giving a desirability value of 0.936. The present study evaluated fruit extract of P. macrocarpa and successfully optimized the formulation of the species-based tablet presenting novel solutions to health-related issues.